2023
DOI: 10.1242/jeb.244863
|View full text |Cite
|
Sign up to set email alerts
|

Non-linear properties of the Achilles tendon determine ankle impedance over a broad range of activations in humans

Abstract: Regulating ankle mechanics is essential for controlled interactions with the environment and rejecting unexpected disturbances. Ankle mechanics can be quantified by impedance, the dynamic relationship between an imposed displacement and the torque generated in response. Ankle impedance in the sagittal plane depends strongly on the triceps surae and Achilles tendon, but their relative contributions remain unknown. It is commonly assumed that ankle impedance is controlled by changing muscle activation and, there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Such differences may be genetic, or related to training and exercise. Another source of variation may be subtle differences in standing posture and baseline ankle torque (Jakubowski et al., 2023 ; Sakanaka et al., 2015 , 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such differences may be genetic, or related to training and exercise. Another source of variation may be subtle differences in standing posture and baseline ankle torque (Jakubowski et al., 2023 ; Sakanaka et al., 2015 , 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The stiffest subject's value was ∼−0. source of variation may be subtle differences in standing posture and baseline ankle torque (Jakubowski et al, 2023;Sakanaka et al, 2015Sakanaka et al, , 2021.…”
Section: F I G U R Ementioning
confidence: 99%
See 1 more Smart Citation
“…In Chapter 4 we compared the estimations of our proposed model-based framework against reference joint torque and stiffness, muscle-and tendon-level stiffness, as well as the displacement of individual muscles [144]. Different calibrations of increasing complexity indicated that it was possible to accurately capture all these biomechanical variables using Hill-type muscle models.…”
Section: Key Contributions Of This Dissertationmentioning
confidence: 99%